Preliminary assessment of a hydrogen farm including health and safety and capacity needs - Alssalehin, Esmaeil; Holborn, Paul; Pilidis, Pericles (MDPI, 2024)
The safety engineering design of hydrogen systems and infrastructure, worker education and training, regulatory compliance, and engagement with other stakeholders are significant to the viability and public acceptance of hydrogen farms. The only way to ensure these are accomplished is for the field of hydrogen safety engineering (HSE) to grow and mature. HSE is described as the application of engineering and scientific principles to protect the environment, property, and human life from the harmful effects of hydrogen-related mishaps and accidents. This paper describes a whole hydrogen farm that produces hydrogen from seawater by alkaline and proton exchange membrane electrolysers, then details how the hydrogen gas will be used: some will be stored for use in a combined-cycle gas turbine, some will be transferred to a liquefaction plant, and the rest will be exported. Moreover, this paper describes the design framework and overview for ensuring hydrogen safety through these processes (production, transport, storage, and utilisation), which include legal requirements for hydrogen safety, safety management systems, and equipment for hydrogen safety. Hydrogen farms are large-scale facilities used to create, store, and distribute hydrogen, which is usually produced by electrolysis using renewable energy sources like wind or solar power. Since hydrogen is a vital energy carrier for industries, transportation, and power generation, these farms are crucial in assisting the global shift to clean energy. A versatile fuel with zero emissions at the point of use, hydrogen is essential for reaching climate objectives and decarbonising industries that are difficult to electrify. Safety is essential in hydrogen farms because hydrogen is extremely flammable, odourless, invisible, and also has a small molecular size, meaning it is prone to leaks, which, if not handled appropriately, might cause fires or explosions. To ensure the safe and dependable functioning of hydrogen production and storage systems, stringent safety procedures are required to safeguard employees, infrastructure, and the surrounding environment from any mishaps.
Keywords: hydrogen farm; alkaline electrolyser; proton exchange membrane electrolyser; hydrogen safety; combined-cycle gas turbine; safety distance; 40 Engineering; 7 Affordable and Clean Energy; 13 Climate Action; 33 Built environment and design; 51 Physical sciences